Risk of dementia in parents of probands with and without the apolipoprotein E4 allele. The EVA study. Issue 7 (1st July 1999) - Danet, S; Brousseau, T; Richard, F; Amouyel, P; Berr, C
Abstract : STUDY OBJECTIVE: Age, family history of dementia and the epsilon 4 allele of the apolipoprotein E gene have been associated with Alzheimer's disease (AD). Considering the strength of APOE-epsilon 4 as a genetic risk factor for AD, this factor might explain a large part of the association between AD and a family history of dementia. Therefore, in the general population, a higher frequency of dementia should be observed among parents of probands with at least one epsilon 4 allele than in parents of probands without this allele. DESIGN, SETTING, AND PARTICIPANTS: The study investigated a sample of 1153 volunteers between 59 and 71 years old, genotyped for the APOE gene, all participating in the EVA study. Dementia in their parents was determined using a self reported questionnaire. MAIN RESULTS: The frequency of dementia in 2164 parents was examined and it was found that 245 were demented. The percentage of demented parents was 13.0% in the subgroup of parents of subjects having one or two epsilon 4 alleles and 10.8% in the other subgroup. The relative risk of dementia among parents according to the APOE-epsilon 4 status of probands, was calculated using a Cox model adjusted for the educational level of parents and their history of stroke: RR = 1.21 (95% CI 0.90, 1.63). CONCLUSION: This lack of association supports the observation that in the general population, APOE-epsilon 4 cannot explain a large part of family history of dementia.